Connecting Ridge - A landing site at the lunar south pole with extended illumination - Gläser, P.; Scholten, F.; De Rosa, D.; Figuera, R. M.; Oberst, J.; Mazarico, E.; Neumann, G. A.; Robinson, M. S. (2014)
Illumination conditions of the lunar south pole are investigated using a 20 m/pixel Digital Terrain Model (DTM) derived from tracks of the Lunar Orbiter Laser Altimeter (LOLA). We examined areas near the south pole, in particular a possible landing site residing on a ridge connecting the de Gerlache and Shackleton craters, referred to as Connecting Ridge [1]. Illumination conditions were simulated at surface level but also at the height of a possible solar panel of a rover or lander, specifically we chose heights of 2 m and 10 m above ground. The chosen time period, over which illumination conditions are simulated, is 19 years exceeding the lunar precessional cycle of 18.6 years. Locations receiving sunlight for 92.3% and 95.66% of the time can be identified at heights of 2 m and at 10 m above ground, respectively. The longest continuous periods in darkness are typically only 3-5 days at these locations, which makes the exclusive use of solar panels over long mission durations achievable.